PENGADAAN TANAH UNTUK PROYEK PEMBANGUNAN MAMMINASATA DAN DAMPAKNYA DI PEDESAAN - Ridha, Muhammad (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
The research is aimed at answering three related questions, either directly or indirectly on the program of large-scale land acquisition on Mamminasata Program in South Sulawesi. These questions are: 1) How does the space structure change after Mamminasata project on land acquisitions at three villages: Samata, Pacci’nongang and Romang Polong?; 2) How does the process and dynamic land acquisition at three village take place?; 3) How does the possibility of conflict take place after the project was done. Those questions will be answered by descriptive qualitative research method. The result shows that there was a correlation between large scale land acquisition on Mamminasata program with spatial change, the rise of land and extensive agrarian conflict. Keywords: development program, Mamminasata, spatial change, land acquisition.